The First Finding of Paulinella chromatophora (Rhizaria, Euglyphida) in Ukraine - Kapustin, D.A. (Вестник зоологии, 2012)
A іtestate amoeba, Paulinella chromatophora Lauterborn, 1895, is recorded for the first time in the fauna of Ukraine. It is illustrated under the light and scanning electron microscope and redescribed.